Quantitative Evaluation of Ankle Instability Using a Capacitance-Type Strain Sensor. (August 2021) - Teramoto, Atsushi; Iba, Kousuke; Murahashi, Yasutaka; Shoji, Hiroaki; Hirota, Kento; Kawai, Makoto; Ikeda, Yuma; Imamura, Rui; Kamiya, Tomoaki; Watanabe, Kota; Yamashita, Toshihiko
Background: Manual evaluation is an important method for assessing ankle instability, but it is not quantitative. Capacitance-type sensors can be used to measure the distance on the basis of the capacitance value. We applied the sensor to the noninvasive device for measuring ankle instability and showed its utility. Methods: First, 5 ankles embalmed by Thiel's method were used in an experiment using a cadaver. The capacitance-type sensor was fixed alongside the anterior talofibular ligament (ATFL) of a specially made brace, and the anterior drawer test was performed. The test had been performed for the intact ankle, with the ATFL transected and with both the ATFL and calcaneofibular ligament (CFL) transected. The anterior drawer distance was calculated by the sensor. Intra- and interinvestigator reliability were also analyzed. Next, as a clinical study, a brace with a sensor was fitted to 22 ankles of 20 patients with a history of ankle sprain. An anterior drawer test at a load of 150 N was conducted using a Telos stress device. The anterior drawer distances measured by the sensor and based on radiographic images were then compared. Results: The mean anterior drawer distances were 3.7 ± 1.0 mm for the intact cadavers, 6.1 ± 1.6 mm with the ATFL transected ( P < .001), and 7.9 ± 1.8 mm with the ATFL and CFL transected ( P < .001). The intrainvestigator intraclass correlation coefficients (ICCs) were 0.862 to 0.939, and the interinvestigator ICC was 0.815. In the experiments on patients, the mean anterior drawer distance measured by the sensor was 2.9 ± 0.9 mm, and it was 2.7 ± 0.9 mm for the radiographic images. The correlation coefficient between the sensor and the radiographic images was 0.843. Conclusion: We quantitatively evaluated anterior drawer laxity using a capacitance-type sensor and found it had high reproducibility and strongly correlated with stress radiography measurements in patients with ankle instability. Capacitance-type sensors can be used for the safe, simple, and accurate evaluation of ankle instability.